The Dual Role of Nod-Like Receptors in Mucosal Innate Immunity and Chronic Intestinal Inflammation - Corridoni, Daniele; Arseneau, Kristen O.; Cifone, Maria Grazia; Cominelli, Fabio (Frontiers in Immunology, 2014)
Nucleotide-binding and oligomerization domain NOD-like receptors (NLRs) are highly conserved cytosolic pattern recognition receptors that play, in combination with toll-like receptors, a critical role in innate immunity and inflammation. These proteins are characterized by a central oligomerization domain termed nucleotide-binding domain, and a protein interaction domain containing leucine-rich repeats. Some NLRs, including NOD1 and NOD2, sense the cytosolic presence of conserved bacterial molecular signatures and drive the activation of mitogen-activated protein kinase and the transcription factor NF-κB. A different set of NLRs induces caspase-1 activation through the assembly of large protein complexes known as inflammasomes. Activation of NLR proteins results in secretion of pro-inflammatory cytokines and subsequent inflammatory responses. The critical role of NLRs in innate immunity is underscored by the fact that polymorphisms within their genes are implicated in the development of several immune-mediated diseases, including inflammatory bowel disease. Over the past few years, the role of NLRs in intestinal homeostasis has been highlighted, however the mechanism by which dysfunction in these proteins leads to aberrant inflammation is still the focus of much investigation. The purpose of this review is to systematically evaluate the function of NLRs in mucosal innate immunity and understand how genetic or functional alterations in these components can lead to the disruption of intestinal homeostasis, and the subsequent development of chronic inflammation.